Hubungan Pemberian ASI Ekslusif, Status Ekonomi, Pelayanan Kesehatan dengan Kejadian Stunting pada Balita Usia 1-5 Tahun di UPTD Puskesmas Tanjung Pinang Kota Jambi Tahun 2022 - Radiah, Radiah; Mansyur, Siti Fatimah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Inhibition episodes in young children can occur due to many factors, one of which is the choice of breast milk, family financial status, and health services. Providing nutrition does not completely depend on the mother's selective breastfeeding and the family's financial status. This research is a logical observational research with a cross sectional methodology conducted at the Tanjung Pinang Community Group Welfare Center, with a sample size of 57 respondents. The results of the research show that there is a relationship between selective breastfeeding, financial status, and welfare services and the frequency of obstacles in young children aged 1-5 years at the Tanjung Pinang Community Group Welfare Center, East Jambi.